Ciborium Forms in Serbian Ecclesiastical Architecture - Marinković, Dimitrije (Arhitektura i urbanizam, 2025)
The primary motive behind this paper is to identify the presence of ciborium structures in Serbian ecclesiastical architecture. The physical scope of the research encompasses, in a broader sense, the Christian temple, and more specifically, the altar space, which is examined through the method of identifying theological symbolism. The sacred topography of the Christian church is interpreted from the standpoint of theological and programmatic significance. The spatial units of the church are briefly analyzed through theological symbolism, in order to gain insight into the origin of their meaning. The research highlights the types of ciboria, both past and present. The typological method points to the existence of various types of ciboria. By determining their theological origin, the study will shed light on the types of ciboria in the liturgical practice of Serbian Orthodox churches throughout history. The functional method will determine their purpose. A descriptive approach provides insight into their architectural and decorative features. The paper examines the way in which their functionality is integrated with visual expression, emphasizing a non-arbitrary interpretation of the corresponding artistic heritage. As part of the development and completion of the altar’s physical structure, the analysis of contemporary examples aims to present them as a contribution to answering the question of their meaningfulness. The method of transposition will consider in detail the ways historical models and aesthetic patterns are used and implemented in contemporary works.
Keywords: architecture; church; Orthodox temple; ciborium